Masculine Domination during Epidemic of Covid-19 in The Sotang’s Village, Tuban: The Perspective of Pierre Bordieu - Faridlatus Sya'adah; Fitri Febriyanti (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2021)
This article aims to discuss the form of masculine domination in the role of women in facing the impact of the Covid-19 pandemic, especially in the social, economic, and cultural fields found in Sotang’s Village, Tambakboyo District, Tuban Regency. Type of this research is descriptive qualitative. The research object was a housewife with a new profession as an onion cutter in the lower middle class environment. The housewife comes from a family affected by Covid-19. Data obtained through observation and semi-structured interviews. The thinking framework used is Pierre Bordieu's perspective on the masculine domination. The masculine domination that was found in the social practices of the Sotang’s Village during the Covid-19 pandemic included: (1) women and onion cutting jobs during the Covid-19 outbreak; (2) female onion cutters as mothers and teachers; (3) space contestation for women onion cutters; (4) poverty and women. The role of women in increasing economic capital cannot be exchanged for symbolic capital. The form of masculine domination followed by symbolic violence as a result of the persecution of women from the lower middle class in the Sotang’s Village during the Covid-19 pandemic has become part of the strengthening of androcentric culture.